1974
DOI: 10.1111/j.1365-2125.1974.tb01696.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Procaine Amide in Man Studied With a New Gas Chromatographic Method

Abstract: A specific gas-chromatographic method was developed for determination of N-acetylprocaine amide in plasma and urine, using 4-amino-N-(2-piperidinoethyl)benzamide as an internal standard. The investigation was performed in 50 cardiac patients who had reached steady-state plasma concentrations of procaine amide. 2 The plasma concentrations of the acetylated metabolite varied between 1.0 and 15.0 mg/ml and were thus of the same order of magnitude as those of the parent drug. Especially high plasma levels of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1976
1976
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Gibson et al 14) reported 7 to 34% N-acetylprocainamide recovery in 24 h in normal volunteers after a single oral dose of procainamide, and Karlsson et al 15) reported 6 to 53% recovery in 24 h in patients who were being given procainamide chronically.…”
mentioning
confidence: 99%
“…Gibson et al 14) reported 7 to 34% N-acetylprocainamide recovery in 24 h in normal volunteers after a single oral dose of procainamide, and Karlsson et al 15) reported 6 to 53% recovery in 24 h in patients who were being given procainamide chronically.…”
mentioning
confidence: 99%
“…The suggestion has been made that the slow acetylators of PA may be at greater risk of developing druginduced side effects (such as the syndrome resembling systemic lupus erythematosus, SLE) as do the slow acetylators of the bimodally acetylated drugs hydralazine, 20 isoniazid, 17, 14,21 and phenelzine. sit has been reported that it may be possible to predict PA phenotype by determining the rate of acetylation of other drugs l2 , 17,22,23 or by measuring the plasma or urinary ratio of NAPA/PA in timed samplesY After our study was completed, one of our patients, R. H., who had been on PA (750 mg every 6 hr) for 1 yr, was readmitted to the hospital with an SLE-like syndrome, probably induced by PA. He complained of migratory arthralgias and arthritis and had a pericardial effusion, pericardial friction rub, fever, positive antinuclear antibody, and 3 positive LE cell preparations…”
Section: Discussionmentioning
confidence: 98%
“…One of the major recent advances in this area has been the discovery of the polymorphic nature of procainamide acetylation (Karlsson, Molin, Norlander & Sjoqvist, 1974;Reidenberg, Drayer, Levy & Warner, 1975) and its relation to toxicity, both shortterm cardiovascular effects (Campbell, Tilstone, Lawson, Hutton & Lawrie, 1976), and induction of lupus erythematosis (Karlsson et al, 1974;Davies, Beedie & Rawlins, 1975). Unfortunately, in the Campbell et al (1976) reported that procainamide interferes with the use of sulphadimidine as a marker for acetylator capacity.…”
Section: Methodsmentioning
confidence: 99%